Municipalization of the Berlin Electric Works - Brooks, Robert C. (Quarterly Journal of Economics, 1915)
Municipalization of the Berlin Electric Works Get access Robert C. Brooks Robert C. Brooks Swarthmore College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 30, Issue 1, November 1915, Pages 188–194, https://doi.org/10.2307/1885810 Published: 01 November 1915